Sosialisasi Fikih Wanita bagi Remaja Desa Balonggemek, Megaluh, Jombang - Hidayah, Nurul; Qosim, Nanang; Pangestu, Noval; Ardiansyah, Al Bustomy; Maulidiyah, Ersa Risma; Chamimah, Siti Nur (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
Thoharah is a problem that is often ignored, especially among the public. Not a few of them ignore it. Therefore, there is a need for regular outreach on this issue, especially regarding menstruation, postpartum and istihadzah. This socialization can provide knowledge and strengthen knowledge in society, especially for teenagers who are growing up. The method used to realize this goal is the Asset Based Community Development (ABCD) theory, which prioritizes the utilization of assets and potential owned by the community and then used as empowering material. The results of this activity are new insights into the science of feminine jurisprudence for teenagers in the Balonggemek environment. Apart from that, the teachings of jurisprudence are embedded in everyday life. The most important thing is the growing awareness of learning about feminine jurisprudence. Keywords: Socialization, Women's Jurisprudence, Teenagers, Balonggemek.